The Effect of Job Satisfaction on the Turnover Intention of PT Berkat Mandiri Expedisi - Yuli Manda Sari (Pusat Riset dan Inovasi Nasional, 2025)
This study examines the effect of job satisfaction on employee turnover intention at PT Berkat Mandiri Expedisi using a descriptive quantitative method with a randomly selected sample of 104 employees. Simple linear regression analysis shows that job satisfaction has a significant influence on turnover intention, with a regression coefficient of -0.450, a significance value of 0.000, and a t-value of -5.294, which is smaller than -t-table (-1.659). Additionally, the standardized coefficient (Beta) of -0.350 indicates that job satisfaction contributes to reducing turnover intention. These findings confirm that the higher the job satisfaction, the lower the employees' intention to leave the company. Therefore, the company should focus on improving employee well-being, better reward systems, and a supportive work environment to reduce turnover rates. Further research is needed to explore other factors that also contribute to turnover intention, such as work pressure, career opportunities, and work-life balance.